Genome-wide association study reveals 18 QTL for major agronomic traits in a Nordic–Baltic spring wheat germplasm - Aleliūnas, Andrius; Gorash, Andrii; Armonienė, Rita; Tamm, Ilmar; Ingver, Anne; Bleidere, Māra; Fetere, Valentīna; Kollist, Hannes; Mroz, Tomasz; Lillemo, Morten; Brazauskas, Gintaras (Frontiers in Plant Science, 2024)
Spring wheat (Triticum aestivum L.) remains an important alternative to winter wheat cultivation at Northern latitudes due to high risk of overwintering or delayed sowing of winter wheat. We studied 9 major agronomic traits in a set of 299 spring wheat genotypes in trials across 12 year-site combinations in Lithuania, Latvia, Estonia, and Norway for three consecutive years. The dataset analysed here consisted of previously published phenotypic data collected in 2021 and 2022, supplemented with additional phenotypic data from the 2023 field season collected in this study. We combined these phenotypic datasets with previously published genotypic data generated using a 25K single nucleotide polymorphism (SNP) array that yielded 18,467 markers with a minor allele frequency above 0.05. Analysis of these datasets via genome wide association study revealed 18 consistent quantitative trait loci (QTL) replicated in two or more trials that explained more than 5 % of phenotypic variance for plant height, grain protein content, thousand kernel weight or heading date. The most consistent markers across the tested environments were detected for plant height, thousand kernel weight and days to heading in 8, 5 and 6 trials, respectively. No beneficial effect of the semi-dwarfing alleles Rht-B1b and Rht-D1b on grain yield performance was observed across the 12 tested trials. Moreover, the cultivars carrying these alleles were low yielding in general. Based on principal component analysis, wheat genotypes developed in the Northern European region clustered separately from those developed at the southern latitudes and markers associated with the clustering were identified. Important phenotypic traits, such as grain yield, days to heading, grain protein content and thousand kernel weight were associated with this clustering of the genotype sets. Interestingly, despite being adapted to the Nordic environment, genotypes in the Northern set demonstrated lower grain yield performance across all tested environments. The results indicate that spring wheat germplasm harbors valuable QTL/alleles, and the identified trait-marker associations might be useful in improving Nordic-Baltic spring wheat germplasm under global warming conditions.